Nano-motor composite material with eccentric core-spinous shell structure and preparation method and application of nano-motor composite material

By developing nanomotor composite materials with an eccentric core-spike shell structure, combining ICG, carbon material and lysate staphylococcienzyme, and using near-infrared light to drive self-heating motion, targeted antibacterial to MRSA biofilm, the complexity of MRSA infection in diabetes trauma and the adverse reactions of antibiotic treatment were solved, and efficient wound healing was achieved.

CN119701008AActive Publication Date: 2025-03-28湖南省职业病防治院
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411888220.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Diabetic trauma, especially foot ulcers, are common and severe. Due to low immune function, infected wound healing is slow, and methicillin-resistant Staphylococcus aureus (MRSA) infection is complex. Existing antibiotic treatments have adverse reactions such as nephrotoxicity and intestinal flora disorders. The antibacterial effect of nanomaterials depends on passive diffusion and is difficult to targeted treatment.

Method used

A nanomotor composite material with an eccentric core-spine-shaped shell structure is developed, combining photosensitizer ICG and carbon material to generate an autothermal driving force under near-infrared light irradiation, and combining lysate staphylococase and ROS to achieve targeting MRSA biofilm.

Benefits of technology

It achieves efficient synergistic antibacterial properties, can specifically target MRSA biofilms, significantly improve antibacterial effects, reduce the generation of drug-resistant strains, and avoid damage to normal tissues through gentle photodynamic effects, and promote diabetic wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701008A_ABST
    Figure CN119701008A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-motor composite material with an eccentric core-spinous shell structure and a preparation method and application thereof.The nano-motor composite material is of a core-shell structure, the core of the nano-motor composite material is composed of a carbon material, the space between the core and the shell is filled with indocyanine green and lysostaphin materials, the shell is composed of a SiO2 carbon material, and the nano-motor composite material is of a spinous porous structure; indocyanine green and lysostaphin are loaded on the surface; and the sphere centers of the core and the shell do not coincide. The nano-motor composite material disclosed by the invention is combined with the photosensitizer ICG and the carbon material in the material under the irradiation of NIR, and the asymmetric eccentric structure of the nano-motor composite material can enable the composite material to be non-uniformly heated to generate self-heating driving force, so that the targeting effect of lysostaphin and ROS on an MRSA biological membrane is realized. The nano motor is applied to preparation of drugs for promoting healing of diabetic wounds, has excellent tissue infiltration capacity and drug delivery efficiency, and shows efficient synergistic antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nanomotor composite material and a preparation method and application thereof, and in particular to a nanomotor composite material with an eccentric core-spiny shell structure and a preparation method and application thereof, belonging to the technical field of antibacterial nanomaterial development. Background Art

[0002] Diabetes mellitus (DM) is a chronic non-infectious disease caused by impaired insulin secretion and utilization, leading to hyperglycemia. DM trauma, especially foot ulcers, are common and severe, and are the main cause of non-traumatic amputation in patients. 15-25% of DM patients worldwide will develop foot ulcers, and 85% of amputees have a history of foot ulcers. The risk of foot ulcer amputation in DM patients is 10-20 times that of non-DM patients. Due to factors such as low immune function, infected wounds heal slowly and may cause systemic complications. DM wound pathogens are diverse, and chronic DM trauma infections often involve methicillin-resistant Staphylococcus aureus (MRSA), which has the characteristics of colonization, invasion, and strong drug resistance. About 15-30% of DM foot ulcer patients may be infected with MRSA, and patients with frequent hospitalizations, multiple antibiotic treatments, deep ulcers, and osteomyelitis are more susceptible to infection.

[0003] At present, the treatment of DM trauma complicated with infection mainly includes anti-infection, wound management, metabolic control, surgical intervention and systemic supportive treatment, among which anti-infection is the key. However, DM trauma, especially long-term open ulcers, are often accompanied by mixed infection of multiple pathogens, which increases the complexity of diagnosis and treatment; in addition, DM patients often have peripheral vascular disease, and insufficient blood supply to local tissues will reduce the concentration of antibiotics at the infected site and weaken its bactericidal effect. In the process of systemic application of antibiotics such as vancomycin, aminoglycosides and other drugs, nephrotoxicity and intestinal flora imbalance are prone to adverse drug reactions. Therefore, anti-infection treatment of DM patients faces many challenges and difficulties.

[0004] Biofilm is an extracellular matrix structure formed by bacteria under stimulation, which is mainly composed of extracellular polymers (EPS). Bacteria are connected through EPS. Surface bacteria can sense the environment, while deep bacteria are dormant. There are nutrient transmission channels in the biofilm. Bacteria adhere to the wound surface through surface molecules and then secrete EPS for stable attachment. However, the biofilm structure is strong and not easily removed by physical means, which can prevent the entry of antibiotics and immune factors. The negative charge structure in EPS can adsorb and neutralize antibiotics, and bacteria in the biofilm can also decompose antibiotics that have penetrated into it, making the treatment of chronic wounds and deep infections with biofilms much more difficult.

[0005] In recent years, lysozyme has attracted widespread attention due to its remarkable efficacy in destroying bacterial cell walls. Unlike traditional antibiotics, lysozyme is an antibacterial hydrolase that naturally exists in biological secretions and fluids (such as saliva, tears, and mucus), and is an important component of the body's nonspecific immune defense. Lysozyme mainly destroys the integrity of bacterial cell walls by hydrolyzing peptidoglycan in bacterial cell walls, causing bacterial cell rupture and death, and has unique advantages in the treatment of Gram-positive bacteria. In combined antibiotic treatment, lysozyme can significantly enhance the penetration ability of antibiotics, improve the killing efficiency of bacteria, and reduce the body's antibiotic load and side effects. In addition, due to its natural decomposition and metabolism characteristics, lysozyme is a safe and effective alternative for some patients who require long-term antibacterial treatment and are intolerant or allergic to antibiotics. However, its clinical application is often limited by enzyme degradation, immunogenicity, bioavailability, and adverse reactions. Therefore, how to effectively improve its utilization rate and reduce side effects is the current difficulty in the application of lysozyme.

[0006] Nanomaterials have been widely used in antibacterial treatment, but the antibacterial effect of nanomaterials depends on passive diffusion and lacks a targeting mechanism, resulting in a decrease in the effective aggregation concentration at the site of infection. In addition, given the existence of biofilms, most common nanomaterials can only stay on the surface of biofilms, showing low antibacterial activity in the treatment of biofilm-related diseases such as chronic wound infections and implant-related infections, while also increasing the risk of drug resistance in pathogens.

[0007] Nanomotors are nanoparticles that can generate autonomous motion under driving force. According to their power source, they can be divided into endogenously driven and exogenously driven nanomotors. In antibacterial treatment, the mechanical force generated by nanomotors can destroy the biofilm matrix, and can also carry antibacterial drugs and release them in the biofilm to improve the bactericidal efficiency and reduce the production of drug-resistant strains. They can also achieve synergistic antibacterial treatment through surface modification. Now many researchers have successfully constructed some multifunctional integrated nanomotor antibacterial platforms by modifying the surface of nanomotors with photosensitizers, magnetic materials, active enzymes, etc. to achieve synergistic antibacterial treatment through photothermal therapy, photodynamic therapy or enzymatic catalytic reactions, but there is a lack of research on targeted and efficient effects against MRSA.

[0008] Photodynamic therapy (PDT) is a method in which photosensitizers (PS) and oxygen interact under near-infrared (NIR) light conditions to produce reactive oxygen species (ROS), which play an important role in a variety of physiological processes. In wound healing, an appropriate amount of ROS can be antibacterial and promote angiogenesis, but high levels of ROS can cause oxidative stress, leading to delayed healing. Therefore, in clinical treatment, it is particularly important to rationally regulate the generation and action of ROS. Indocyanine green (ICG) is a widely used photosensitizer (PS) with characteristics in the near-infrared region, which can achieve "integrated diagnosis and treatment", has good biocompatibility and low risk of phototoxicity, and has an antibacterial effect in wound healing, but free ICG has a short half-life and is easily decomposed, and improving its utilization rate is a difficulty in application.

[0009] Therefore, there is an urgent need to develop a composite material with biomembrane permeability and high antibacterial activity for the preparation of drugs for the treatment of DM wounds infected with MRSA. Summary of the invention

[0010] In view of the problems existing in the prior art, the first object of the present invention is to provide a nanomotor composite material, which has a special eccentric core-spiny shell structure. Under the irradiation of NIR, the photosensitizer ICG and carbon material in the material are combined, and its asymmetric eccentric structure can make the composite material unevenly heated, generate self-heating driving force, and achieve the targeted effect of lysostaphin (Ly) and ROS on MRSA biofilm. The nanomotor has excellent tissue penetration ability and drug delivery efficiency, and exhibits efficient synergistic antibacterial performance.

[0011] The second object of the present invention is to provide a method for preparing a nanomotor composite material with an eccentric core-spine-like shell structure. The method comprises aminopropylating carbon-SiO2@carbon nanoparticles with an eccentric core-spine-like shell structure, and utilizing electric charge to load ICG with photothermal effect and biomembrane-targeted lysostaphin on the surface of the shell structure, thereby increasing the loading capacity and overall antibacterial properties of the composite material.

[0012] The third object of the present invention is to provide an application of a nanomotor composite material with an eccentric core-spiny shell structure, which is used in the preparation of drugs to promote diabetic wound healing. By combining photothermal, photodynamics, and lysostaphin, the nanomotor composite material is driven to move autonomously by near-infrared light, which can specifically target MRSA biofilms and show significant synergistic effects in antibacterial, anti-inflammatory and promoting tissue repair. The composite material of the present invention can produce mild photodynamic effects when used in conjunction with special NIR light treatment, thereby avoiding damage to normal tissues.

[0013] In order to achieve the above technical objectives, the present invention provides a nanomotor composite material with an eccentric core-spine-like shell structure, wherein the nanomotor composite material has a core-shell structure, wherein the core is composed of a carbon material, the core and the shell are filled with indocyanine green and lysostaphin, the shell is composed of a SiO2@carbon material, has a spiny porous structure, and is loaded with indocyanine green and lysostaphin on the surface; the centers of the core and the shell do not overlap.

[0014] The nanomotor composite material of the present invention skillfully combines an eccentric core-spiny shell structure with ICG having a photothermal effect, a carbon material, and Ly having targeting to MRSA biofilms, and synergistically improves the antibacterial performance of the nanomotor composite material through structure and composition. Specifically, under the irradiation of NIR, the nanomotor composite material of the present invention has photothermal effect because both ICG and the carbon material constituting the core-shell structure matrix have photothermal effect, but the intensity of the photothermal effect of the two is different: the outer shell with both ICG and carbon material has the strongest photothermal effect; the photothermal effect intensity of ICG filled between the core and shell is second, and the photothermal effect of the carbon material with the eccentric core is the weakest, thereby causing uneven heating of the composite material and generating self-heating driving force, so that the composite material can move along the temperature gradient direction; in the application of preparing drugs to promote diabetic wound healing, when the drug contacts MRSA through self-heating drive, the Ly loaded on the surface of the nanomotor composite material and the internal Ly released through the thorny porous structure can target and destroy the biofilm of MRSA, causing MRSA cells to rupture and die; in addition, under the irradiation of NIR, the ICG in the composite material can produce a large amount of ROS, further enhancing the antibacterial effect and promoting wound healing.

[0015] The present invention also provides a method for preparing a nanomotor composite material having an eccentric core-spine-like shell structure, the method comprising: modifying the carbon-SiO2@carbon nanoparticles having an eccentric core-spine-like shell structure with aminopropyl groups by surface grafting to obtain aminopropylated carbon-SiO2@carbon nanoparticles; mixing the aminopropylated carbon-SiO2@carbon nanoparticles, indocyanine green and lysostaphin to obtain a nanomotor composite material (CSIL) having an eccentric core-spine-like shell structure;

[0016] The preparation process of the carbon-SiO2@carbon nanoparticles with an eccentric core-spine shell structure is as follows: aldehyde resin microspheres, resorcinol, formaldehyde and tetraethyl orthosilicate are reacted A to obtain nanospheres with a core-shell structure, phenolic resin-SiO2@phenolic resin; an etchant is added to the phenolic resin-SiO2@phenolic resin for hydrothermal reaction to obtain partially etched phenolic resin-SiO2@phenolic resin nanospheres; the partially etched phenolic resin-SiO2@phenolic resin nanospheres are obtained after carbonization.

[0017] In the technical scheme of the present invention, firstly, during the reaction A, the polycondensation reaction of resorcinol and formaldehyde and the hydrolysis reaction of tetraethyl orthosilicate occur synchronously, so that the newly generated phenolic resin microspheres and silicon dioxide are deposited on the surface of the original aldehyde resin microspheres to form nanospheres with a core-shell structure of phenolic resin-SiO2@phenolic resin (RF-SiO2@RF), and then a thorn-like porous structure is formed on the shell through the hydrothermal reaction and the etching action of the etchant, and a cavity appears inside; during the carbonization process, due to the density difference between the core and the shell, the internal core structure becomes smaller, and an eccentric core structure is formed under the action of gravity to obtain carbon-SiO2@carbon nanoparticles (C-SiO2@C). Secondly, after the surface of C-SiO2@C is modified with aminopropyl, the material is positively charged, while ICG is negatively charged and Ly is positively charged. The two are loaded in turn through electrostatic action, and ICG and Ly can be filled in the cavity between the core and the shell through the porous structure, so the method of the present invention can significantly increase the load of the nanomotor.

[0018] As a preferred solution, the phenolic resin microspheres are obtained by polycondensation reaction of resorcinol, formaldehyde and water under the action of an alkaline catalyst. The solid-liquid ratio of resorcinol to formaldehyde is 0.3 g: (0.4-0.5) mL, and the reaction temperature is room temperature. The alkaline catalyst includes commonly used alkalis such as sodium hydroxide and potassium hydroxide.

[0019] As a preferred solution, the process of surface grafting modification with aminopropyl groups is as follows: after dispersing carbon-SiO2@carbon nanoparticles, (3-aminopropyl)triethoxysilane is added for grafting reaction; the dispersion is promoted by ultrasound, and the dispersion solvent is ethanol.

[0020] As a preferred solution, the solid-liquid ratio of the carbon-SiO2@carbon nanoparticles and (3-aminopropyl)triethoxysilane is 15 mg: (0.15-0.3) mL. The present invention can comprehensively control the degree of aminopropylation by regulating the solid-liquid ratio of the two, so as to facilitate subsequent reactions. If the amount of (3-aminopropyl)triethoxysilane used is too small, the degree of aminopropylation on the surface of the carbon-SiO2@carbon nanoparticles is insufficient, and the positive charge on the surface is insufficient, which will not only lead to a decrease in the loading amount of ICG and Ly, but also excessive carbon-SiO2@carbon nanoparticles in the solution will produce partial agglomeration; and when the amount of (3-aminopropyl)triethoxysilane used is too much, it may adhere to the surface of the nanoparticles, thereby affecting the pore structure of the nanoparticles.

[0021] As a preferred solution, the conditions for the surface grafting modification of aminopropyl groups are: temperature of 50-60° C. and time of 10-12 h.

[0022] As a preferred solution, the mass ratio of the aminopropylated carbon-SiO2@carbon nanoparticles, indocyanine green and lysostaphin is 2:(0.125~2):(0.125~2). The present invention can comprehensively control the various properties of the nanomotor through the mass ratio of aminopropylated carbon-SiO2@carbon nanoparticles, indocyanine green (ICG) and lysostaphin (Ly). In terms of photosensitivity, when the amount of ICG is small, the amount of photothermal and reactive oxygen (ROS) generated under near-infrared irradiation is reduced, and the efficiency of light energy conversion is reduced; when the amount is large, it will cause an imbalance in the internal structure and affect light propagation and conversion. In terms of antibacterial properties, if the proportion of Ly is low, the ability to target and destroy MRSA biofilms is weak and the antibacterial effect is poor; if the proportion is high, it will affect the stability of the nanomotor and thus indirectly affect the antibacterial properties. The ICG content is also affected by the mass ratio, which in turn affects the amount of ROS generated and the antibacterial properties. In terms of healing performance, the mass ratio affects the balance of interactions between components. Too high or too low a ratio of ICG or Ly will break the balance and affect the overall performance of the nanomotor in wound healing.

[0023] As a preferred solution, the mixing condition is: stirring at room temperature for 24 to 48 hours. Further preferably, in the mixing process of the present invention, aminopropylated carbon-SiO2@carbon nanoparticles and ICG are first mixed for 20 to 24 hours, and then Ly is added and mixed for 20 to 24 hours. Through such a mixing method, it can be further ensured that ICG and Ly can be grafted onto carbon-SiO2@carbon nanoparticles in sequence through charge action.

[0024] As a preferred solution, the conditions of reaction A are: room temperature, reaction time 5-6 hours; the conditions of the hydrothermal reaction are: 70-80°C, time 0.5-2 hours, and the etchant includes Al(NO3)3 solution. By controlling the temperature and time during the hydrothermal reaction, the degree of etching of the shell can be controlled under the action of the etchant to form a porous structure. The concentration of the etchant is 1-2 mol L -1 , the volume is 100~200mL.

[0025] As a preferred solution, the carbonization conditions are: temperature of 500-550°C and time of 2-3 hours. The present invention can convert phenolic resin into carbon material by carbonization. When the carbonization temperature is too low or the time is too short, carbonization cannot be complete; when the carbonization temperature is too high, the material may be burned and deformed.

[0026] Finally, the present invention also provides an application of a nanomotor composite material with an eccentric core-spiny shell structure, which is used to prepare drugs for promoting diabetic wound healing. By combining photothermal, photodynamics, and lysostaphin, near-infrared light is used to drive the autonomous movement of the nanomotor, which can specifically target MRSA biofilms and show significant synergistic effects in antibacterial, anti-inflammatory, and promoting tissue repair.

[0027] As a preferred solution, the drug comprises a nanomotor composite material having an eccentric core-spine shell structure, physiological saline and excipients. The excipients include excipients commonly used in injection preparations such as phosphate buffer, phenol, glucose and the like.

[0028] As a preferred solution, the drug is an injection preparation, more preferably a pharmaceutically acceptable local injection preparation. The specific use process is: during use, physiological saline can be used to disperse the nanomotor composite material; and the obtained dispersed solution is then administered by injection.

[0029] As a preferred solution, the nanomotor composite material with an eccentric core-spine shell structure is not less than a pharmaceutically effective amount.

[0030] As a preferred solution, the drug has a photothermal effect, and infrared light is used in the early stage of the drug action process, and no infrared light is used in the later stage. Through this special light, it can effectively promote the nanomotor composite material to release 1O2 to kill bacteria, and will not produce excessive ROS to damage normal tissues, which is beneficial to the recovery of diabetic trauma.

[0031] As a preferred solution, the power of the infrared light irradiation is 0.3-1.2 W / cm 2 , the time is 100 to 600 seconds.

[0032] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0033] 1) The nanomotor composite material provided by the present invention has a special eccentric core-spiny shell structure. Under the irradiation of NIR, the photosensitizer ICG and carbon material in the material are combined. Its asymmetric eccentric structure can make the composite material unevenly heated, generate self-heating driving force, and achieve the targeted effect of lysostaphin (Ly) and ROS on MRSA biofilm. The nanomotor has excellent tissue penetration ability and drug delivery efficiency, and shows efficient synergistic antibacterial therapeutic performance.

[0034] 2) The preparation method of the present invention is simple, the reaction conditions are relatively mild, the cost is low, the application prospects are broad, and large-scale preparation can be carried out. Moreover, the method can significantly increase the loading capacity of the nanomotor for ICG and Ly.

[0035] 3) The nanomotor composite material of the present invention is used to prepare drugs for promoting diabetic wound healing. By combining photothermal, photodynamic and lysostaphin, the nanomotor composite material is driven by near-infrared light to move autonomously, which can specifically target MRSA biofilms and show significant synergistic effects in antibacterial, anti-inflammatory and promoting tissue repair.

[0036] 4) The material of the present invention is used to prepare drugs for promoting diabetic wound healing. When the drug is used, the nanomotor composite material produces a mild photodynamic effect through the method of early short-term NIR light irradiation and later no NIR light irradiation. This can effectively release 1O2 to kill bacteria without generating excessive ROS to damage normal tissues, which is beneficial to the recovery of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The microscopic morphology of CS and CSIL prepared in Example 1 of the present invention, wherein: Figure 1 (a) and Figure 1 (b) SEM images of CS and CSIL, respectively; Figure 1 (c) and Figure 1 (d) TEM images of CS and CSIL; Figure 1 (e)~ Figure 1 (j) is the EDS scan of CSIL.

[0038] Figure 2 The UV absorption spectra of ICG and Ly at different concentrations and the residual ICG and Ly in the solution after loading in Example 1, wherein: Figure 2 (a) is the UV-visible spectra of ICG at different concentrations and residual ICG in the CSIL solution in Example 1; Figure 2 (b) UV-visible spectra of residual Ly in solutions of different Ly concentrations and CSIL.

[0039] Figure 3 The loading rate and Zeta potential of the nanomotor composite material prepared in Example 1 of the present invention are measured, wherein: Figure 3 (a) The loading rate of ICG and Ly on CS nanomotors; Figure 3 (b) Zeta potential of CS, CSI and CSIL.

[0040] Figure 4 The photothermal effect of CS, CSI and CSIL prepared in Example 1 of the present invention; wherein, Figure 4 (a) CS (200 μg mL -1 ); Figure 4 (b) CSI (200 μg mL -1 ); Figure 4 (c) CSIL (200 μg mL -1 ) temperature changes; Figure 4 (d) is 1.2Wcm -2 Temperature rise variation of CSIL with different concentrations under power density; Figure 4(e) Power density is 1.2 W cm -2 Temperature changes of CS, CSI and CSIL under the conditions; Figure 4 (f)~ Figure 4 (h) Photothermal cycle curves of CS, CSI, and CSIL, respectively; Figure 4 (i) is the relationship between illumination time and -lnθ.

[0041] Figure 5 The absorbance of DPBF obtained in Example 1 of the present invention under near-infrared laser (808 nm) irradiation changes with time, wherein: Figure 5 (a) is the absorbance change of CSI+NIR; Figure 5 (b) is the absorbance change of CSIL+NIR.

[0042] Figure 6 The motion trajectories of the CSIL nanomotor prepared in Example 1 of the present invention under different laser powers are shown.

[0043] Figure 7 Schematic diagram of the Y-tube experiment used in the present invention; wherein, Figure 7 (a) is the schematic diagram of the Y-type tube. Figure 7 (b) is the red fluorescence distribution at the bifurcation of the Y-shaped tube. Figure 7 (c) Comparison of red fluorescence accumulation of Y-terminal MRSA and E. coli.

[0044] Figure 8 This is a confocal microscope image of the binding of the CSIL nanomotor prepared in Example 1 of the present invention with MRSA and E.Coli.

[0045] Fig. 9 is the colony plating data of each group in Example 1 of the present invention, wherein, Fig. 9 (a) is a representative plate of colonies isolated from MRSA biofilms in each group; Fig. 9 (b) is the number of MRSA colonies in each group; Fig. 9 (c) is the survival rate of MRSA in each group, and ns represents no significant statistical difference, ** represents p<0.01, and *** represents p<0.001. Among them, the control group represents the blank control group with PBS added.

[0046] Fig.10 The scanning electron microscope images of MRSA biofilm destruction in each group of Example 1 of the present invention are shown.

[0047] Fig.11 The materials of each group in Example 1 of the present invention are further used to prepare drugs for wound healing in mice experiments, wherein: Fig.11(a) Wound photos of PBS, CS, CSI+NIR, CSIL, CSIL+NIR, and Van groups after treatment for 0, 4, 8, 12, and 16 days. Scale bar: 8 mm. Fig.11 (b) The wound healing traces of different treatment groups during the 16-day treatment period; Fig.11 (c) The percentage change of wound area in different treatment groups, *** represents P < 0.001.

[0048] Fig.12 Schematic diagram of the process of preparing a nanomotor composite material with an eccentric core-spine shell structure according to Example 1 of the present invention, wherein RFR represents RF-SiO2@RF and Etched RFR represents partially etched RF-SiO2@RF. DETAILED DESCRIPTION

[0049] The following examples are only specific descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of implementation of the present invention. For ordinary technicians in the technical field, any improvements made without departing from the present invention should be deemed to be within the scope of protection of the present invention.

[0050] Example 1

[0051] (1) Preparation of C-SiO2@C nanoparticles

[0052] Ultrapure water (20 mL), anhydrous ethanol (140 mL) and NaOH (1.0 mol L -1 The mixture of 10 mL (10 mL) was placed in a 250 mL round-bottom flask. Subsequently, resorcinol (0.3 g) and formaldehyde (0.42 mL) were added and stirred at room temperature for 6 h to obtain phenolic resin RF microspheres.

[0053] Next, tetraethyl orthosilicate (TEOS, 0.6 mL) was added to the round-bottom flask containing the RF microspheres and stirred for 8 min, followed by the addition of resorcinol (0.8 g) and formaldehyde (1.12 mL) and the reaction was stirred for 5 h. The precipitate was filtered and washed with ethanol and ultrapure water for 3 times, respectively, and the product was dried at 60 ° C under vacuum conditions for 12 h. In this way, a layer of RF and SiO2 compounds was deposited on the surface of the RF microspheres obtained in the previous step, forming nanospheres RF-SiO2@RF with a core-shell structure (core is RF, shell is a mixture of RF+SiO2).

[0054] The prepared RF-SiO2@RF (100 mg) was added to Al(NO3)3 (2.0 mol L -1, 100 mL) aqueous solution, transferred to a hydrothermal reactor, reacted at 80 °C for 2 h, cooled to room temperature, centrifuged, washed with water three times, and vacuum dried at 60 °C for 10 h to obtain partially etched RF-SiO2@RF nanospheres.

[0055] Finally, the etched RF-SiO2@RF nanospheres were placed in a tubular furnace and heated to 550°C in a nitrogen environment for 2 hours of carbonization. Finally, C-SiO2@C (CS) nanoparticles with an eccentric core-spine shell structure were obtained.

[0056] (2) Preparation of CSIL nanomotors

[0057] In order to improve the loading performance of CS, CS was surface modified. CS (15 mg) was added to anhydrous ethanol (25 mL) and ultrasonicated for 30 min to ensure that CS was completely dispersed. Then (3-aminopropyl) triethoxysilane (APTES, 0.15 mL) was added and stirred at 60 ° C for 12 h. After the above reactants were cooled to room temperature, they were washed three times with ethanol and dried at 50 ° C to obtain aminopropylated CS nanoparticles.

[0058] Aminopropylated CS (2 mg) and ICG (2 mg) were added to water (1 mL) and mixed, stirred at 25 ° C for 24 h, washed and dried under vacuum at room temperature. ICG-loaded CS nanoparticles (CS@ICG, CSI) were obtained. Then, CSI (2 mg) and lysostaphin (Ly, 2 mg) were added to 1 mL of water and stirred overnight at the same room temperature. Finally, the nanospheres loaded with lysostaphin were washed with water and vacuum dried overnight to obtain an eccentric core-spine shell structured nanomotor composite (CSIL) co-loaded with ICG and Ly.

[0059] In order to observe the surface morphology of CS and CSIL, SEM, TEM and EDS scanning were performed on CS and CSIL prepared in Example 1. The results are as follows: Figure 1 .like Figure 1 (a) and Figure 1 As shown in (b), both CS and CSIL have a uniform spherical structure with a diameter of about 250 nm. Figure 1 (c) and Figure 1 As shown in (d), both CS and CSIL have an eccentric core-spiny shell internal structure. After loading ICG and Ly, the surface of CSIL becomes rougher, but its overall structure does not change compared with CS. Figure 1 (e)~ Figure 1 (j) shows that C and Si elements are evenly distributed in the core and shell. In addition, S and N elements contained in APTES, ICG, and Ly appear in both the core and shell, indicating that ICG and Ly are successfully loaded onto the CS motor.

[0060] ICG and Ly with different concentration gradients were prepared (the concentrations of the two were 2, 1, 0.5, 0.25 and 0.125 mg mL -1 ) solution and measure its UV absorption intensity at different concentrations. Then prepare 2mgmL -1 After the CSI and aminopropylated CS solutions were prepared (i.e., under the conditions of Example 1), they were stirred overnight without washing. The ICG and Ly remaining in the solution that were not bound to CS or CSI were measured by UV-visible spectrophotometer to determine the loading amount. The results are shown in Figure 2 .like Figure 2 (a) and Figure 2 As shown in (b), the characteristic absorption peaks of ICG and Ly are located at 800 nm and 280 nm, respectively, and the UV absorption peak decreases as the concentration decreases. The concentrations of residual ICG and Ly in the solution are significantly reduced, indicating that ICG and Ly are successfully loaded on CS.

[0061] At the same time, prepare 500 μg mL -1 The zeta potential of the samples was measured by CS, CSI and CSIL solutions. The loading rate was determined by UV-visible spectroscopy. According to the amount of ICG and Ly remaining in the supernatant, the loading rates of ICG and Ly were calculated to be 52% and 82%, respectively (Fig. Figure 3 a). In addition, the Zeta potential of the surface-modified CS was 10.33±0.23 mV, and the potential of CSI after loading ICG changed to -6.93±0.29 mV. After loading positively charged Ly, the CSIL potential increased significantly to 11.72±0.38 mV, which once again verified the successful loading of ICG and lysostaphin on CS ( Figure 3 b).

[0062] Photothermal and photodynamic effects of CSIL nanomotors Photothermal and photodynamic performance research:

[0063] First, prepare 200 μg mL -1 The CS, CSI, and CSIL solutions were used at different power densities (0.3, 0.6, 0.9, and 1.2 W cm -2 ) with near-infrared light (wavelength 808nm) and use an infrared thermal imager to record temperature changes every 30 seconds until the temperature stabilizes. The results are as follows: Figure 4 (a)~ Figure 4 (c). When 1.2W cm -2After 10 minutes of irradiation, the temperatures of CS and CSI increased from 25°C to 31.3 and 41.2°C, respectively. When CSI was further loaded with Ly, its maximum temperature also rose to 40.3°C, indicating that the loading of Ly had little effect on the photothermal performance of CSIL. With the increase of power density, the photothermal efficiency increased significantly. The optimal power density was 0.9-1.2 Wcm -2 .

[0064] Secondly, at a fixed optical power density of 1.2 W cm -2 The results showed that CS, CSI and CSIL could be activated at different concentrations (0, 50, 100 and 200 μg mL -1 ) temperature changes, the irradiation time is 10min, the results are as follows Figure 4 (d) As shown in the figure, the photothermal performance of CSIL also shows concentration dependence. As the concentration increases, the maximum temperature of CSIL also increases.

[0065] Finally, to evaluate the photothermal stability of CS, CSI, and CSIL, a power density of 1.2 W cm -2 200 μg mL -1 The nanomotor solution was irradiated for 5 minutes, and then the NIR laser was turned off. After the aqueous solution cooled naturally for 5 minutes, the NIR was turned on again for 5 minutes, and the "on-off" cycle was repeated 5 times. The heating curve is shown in Figure 4 (e), the photothermal cycle curve is as follows Figure 4 (f)~ Figure 4 (h) As shown in the figure, in the photothermal cycling experiment, CS, CSI, and CSIL all exhibited excellent photothermal stability and cyclability.

[0066] In order to calculate the light-to-heat conversion efficiency of CSIL, the following formula is used:

[0067]

[0068] θ=(TT s ) / (T max -T s )

[0069] τ=-t / lnθ

[0070] HkDJ p / τ

[0071] Where η is the photothermal conversion efficiency (%); h is the heat transfer coefficient; S is the surface area of ​​the container used (cm 2 );T max is the highest temperature (40.3°C) reached by the nanomotor after heating and stabilization; T Sis the ambient temperature (25°C); I is the laser power density (1.2 W cm) of the NIR laser (808 nm) used. -2 );A 808 For CSIL nanomotors (200 μg mL -1 ) is the absorption value at 808 nm under ultraviolet measurement (0.191); θ is the dimensionless driving force temperature; τ is the heat transfer time constant; t is the time (s) of the hydrogel during the cooling process; m is the mass of the nanomotor during the measurement (0.5 g); C P is the heat capacity of water (4.2 Jg -1 ). According to the formula and Figure 4 (i) The calculated τ of the CSIL nanomotor is 171.08, and the CSIL photothermal conversion efficiency η is subsequently calculated to be 46.6%. The above results show that the CSIL nanomotor has light power density and concentration dependence, and has excellent photothermal conversion performance and photothermal stability.

[0072] The DPBF probe can be used to detect 1O2 produced by ICG under NIR irradiation, because it can react with 1O2 to form endoperoxides, and the absorption peak of DPBF in ultraviolet light is around 410nm. In order to clarify the ability of CSI and CSIL to produce 1O2, 50μL of DPBF fluorescent probe (1mg mL -1 ) solution was added to 2.9 mL of 50% ethanol solution, and then 50 μL of 2 mg mL -1 The absorbance of the mixed solution at 410 nm after irradiation for 0, 1, 2, 4, 6, 8, 10 and 12 min was measured under near-infrared irradiation at 808 nm. Figure 5 (a) and Figure 5 (b) If Figure 5 As shown in (a), DPBF and CSI (200 μg mL -1 The typical absorption peak of the mixed solution of ) at 410nm gradually weakened over time, indicating the efficient production of 1O2. Figure 5 As shown in (b), the ability of CSIL to produce 1O2 remains unchanged compared with CSI, indicating that loading Ly has no effect on the photodynamic properties of CSIL nanomotors.

[0073] Research on the motion performance of CSIL nanomotors:

[0074] In order to detect the motion performance of the nanomotor, an inverted fluorescence microscope was used to record and observe the motion trajectory of the CSIL nanomotor under different light intensity conditions. Figure 6As shown in the figure, when there is no laser irradiation, the CSIL nanomotor basically moves in place, showing limited and irregular Brownian motion. However, as the light intensity increases, the diffusion range of the nanomotor gradually expands, the motion trajectory is significantly extended, and it has significant motion ability.

[0075] Study on the targeting performance of CSIL nanomotors:

[0076] In order to verify the targeting function of CSIL nanomotors on MRSA bacteria, a Y-tube experiment was performed. The specific operation is as follows: CSIL labeled with red dye RhB was co-cultured with MRSA and E. coli for 1 hour, and the above suspension was centrifuged at 600rpm to remove CSIL that was not bound to bacteria. Finally, the binding of CSIL with MRSA and E. coli was observed under a laser confocal microscope. The Y-tube consists of a liquid storage chamber (I) at the starting part and branch chambers (II) and (III), as well as a main road and two road branches. 0.5% agarose gel was pre-implanted in chambers (II) and (III) to prevent bacteria from retrograde, and then 10 μL of MRSA and E. coli (108 CFU mL -1 ) overnight, followed by the addition of 50 μL RhB-labeled CSIL (200 μg mL -1 ) solution was dispersed in the reservoir (I), and the (I) area was irradiated with near-infrared light. The red fluorescence in the channel and the fluorescence intensity comparison in the reservoirs (II) and (III) were observed using a confocal microscope. The results are shown in Figure 2. Figure 7 .

[0077] like Figure 7 As shown in (a), a CSIL solution containing RhB dye is dripped into the entrance of the Y-tube (I), and pre-cultured MRSA (II) and E. coli (III) are placed at both ends of the Y-tube. Then, NIR irradiation (808nm) (I) chamber is used to light-drive the CSIL. Under a confocal microscope, red nanomotors can be seen moving, forming a large area of ​​red fluorescence in the main trunk. As the nanomotors move to the bifurcation of the Y-tube, it can be observed that at the bifurcation of the Y-tube, the fluorescence intensity of MRSA in the upper right corner is significantly higher than that of E. coli in the lower right corner ( Figure 7 (b)). Moreover, over time, a significant accumulation of CSIL fluorescence intensity can be seen in chamber (II), while there is almost no fluorescence in chamber (III). Figure 7 (c)). However, it can be seen that at the bifurcation of the Y-shaped tube, a small number of nanomotors also tend to move to the lower right chamber (III), which may be due to the inertia of the nanomotors.

[0078] In order to more intuitively demonstrate the targeting of CSIL nanomotors to MRSA, CSIL was co-cultured with bacteria. The specific operation was as follows: the activated MRSA and E. coli were stained with the dye STOY9 green fluorescent nucleic acid dye for 30 minutes, and then the bacterial suspension was washed with PBS until the supernatant was colorless to remove unstained bacteria. At the same time, the red dye Rhodamine B (RhB) was mixed with CSIL 24 hours in advance and then washed for 12 hours to remove excess unbound dye. The stained CSIL was then co-cultured with MRSA and E. coli for 1 hour, and about 10 μL of 0.5% agarose heated in a water bath at 60°C was added to the slide. After waiting for 5 minutes, about 1 μL of the bacterial solution mixture was added, and the binding of CSIL and bacteria was observed under a confocal laser microscope. The results are shown in Figure 2. Figure 8 .

[0079] Depend on Figure 8 As shown, confocal microscopy observed that the red fluorescent CSIL nanomotor bound and overlapped with most of the green fluorescent MRSA, indicating that it bound to MRSA. However, there was almost no binding and overlap between the green fluorescent E. coli and the CSIL nanomotor, indicating that CSIL did not specifically bind to E. coli.

[0080] The above results prove that compared with E. coli, CSIL has a specific targeting effect on MRSA through near-infrared propulsion, laying the foundation for subsequent targeted antibacterial treatment of MRSA and DM wound healing treatment.

[0081] Study on the penetration performance of CSIL nanomotors into biomembranes:

[0082] In order to evaluate the effect of CSIL nanomotors on the removal of MRSA biofilm, a biofilm coating experiment was performed. The specific operation was as follows: 500 μL of MRSA bacterial solution (108 CFU mL -1 After 24 hours, TSB was used to replace the medium. After 48 hours of culture, a biofilm was formed and the TS in vitro antibacterial test medium B on the biofilm was discarded. Then, 500 μL of PBS, CS, CSI, and CSIL solutions (200 μg mL -1 ), incubated in a constant temperature box for 4 h, and then irradiated with 808 nm NIR (1.2 W cm -2) for about 10 minutes. While irradiating, use near-infrared to monitor the temperature in the well plate to ensure that the temperature does not exceed 45°C. Incubate again for 2 hours after irradiation. Then take out the well plate and shake it on a vortex instrument to completely shake and disperse the biofilm. Take 100μL of the suspension of bacterial solution and drug in each group and add it to a 96-well plate. Take 20μL of the original solution and add 180μL PBS to dilute it by 1 order of magnitude, and then dilute it step by step. Take 100μL of the diluted bacterial solution and place it in the middle of the solidified agarose plate, then spread it evenly with a coating stick. After the bacterial solution is air-dried, turn the culture dish upside down and culture it in a 37°C incubator overnight. Take pictures and count the colonies after 16 hours. Repeat the above experimental steps more than three times, and use the following formula to calculate the corresponding bacterial survival rate of each group:

[0083] Bacterial survival rate (%) = number of surviving bacteria in each experimental group / number of surviving bacteria in the control group (%)

[0084] Agar plating and bacterial counts of the remaining biofilm were performed, such as Fig. 9 The agar plate count results showed that in the groups without NIR irradiation, the PBS, CS, and CSI groups had a large number of colonies, with the numbers being 1.40, 1.34, and 1.31×108 CFUmL, respectively. -1 , while the colony count of CSIL was significantly reduced to 4.16×107 CFU mL -1 After the introduction of light, the colony counts in the PBS and CS groups were 1.34 and 1.28×108 CFU mL -1 Compared with the corresponding group without NIR treatment, the number of colonies did not decrease significantly. Compared with the CSI group, the number of colonies in the CSI+NIR group was 7.12×107CFU mL –1 There was a significant decrease in the number of colonies (P < 0.01). The number of colonies in the CSIL + NIR group was only 4.33 × 105 CFU mL –1 , which is much lower than other groups using NIR (P < 0.001). At the same time, the survival rate of the colonies was statistically analyzed, and it was found that there was no significant difference in the antibacterial rate between the control group and the CS group regardless of whether NIR was used or not. Compared with the 93.3% survival rate of the CSI group, the survival rate of the CSI+NIR group was about 51.1% (P < 0.01). Compared with the 29.6% survival rate of the CSIL group, the bacterial survival rate of the CSIL+NIR group was only about 0.31% (P < 0.001), which was significantly lower than the survival rate of other groups treated with NIR (P < 0.001). This shows that CSIL nanomotors driven by near-infrared light have a significant bactericidal effect on MRSA ( Fig. 9 c).

[0085] A silicon wafer was placed in a 48-well plate in advance, and MRSA bacterial solution was also added. After 48 hours of culture, a biofilm was formed on the silicon wafer. The grouping and treatment were consistent with the plate coating experimental steps. After treatment, 200 μL of glutaraldehyde (2.5%) was added to each well for fixation overnight. Subsequently, 200 μL of ethanol with different concentration gradients (10%, 30%, 50%, 70%, 90% and 100%) was used for step-by-step dehydration, of which 100% ethanol was used for dehydration twice, and each dehydration time was 15 minutes. After dehydration, it was air-dried overnight and then sprayed with gold. The morphology of each group of biofilms was observed under SEM and photographed for preservation. The results are shown as follows: Fig.10 .

[0086] like Fig.10 As shown in the figure, the MRSA spherical bacteria in the control group and the CS group were intact, and the biofilm showed a complete structure of stacked layers. When treated with CSI+NIR, there was a little swelling on the bacterial surface, but no obvious bacterial fragments were seen, indicating that the biofilm was initially dissipated. In the CSIL group and the CSIL+NIR group, large areas of cell death were visible, especially a large number of bacterial fragments were widely distributed in the CSIL+NIR group, the MRSA bacteria were distorted and fragmented, and the multi-layer three-dimensional structure of the biofilm basically disappeared. Based on the above results, the ability of CSIL to destroy MRSA biofilm and bacterial structure in vitro is more intuitively demonstrated.

[0087] Study on the performance of CSIL nanomotor composite materials in treating wounds of DM mice with MRSA infection:

[0088] In order to avoid excessive ROS production, a cascade mild photodynamic therapy strategy was adopted, and the treatment was divided into the following two steps: First, near-infrared (NIR) was used to continuously irradiate the wound surface for 3 days, and the ROS produced by ICG, together with Ly, removed the surface layer of the biofilm on the wound. Afterwards, without the use of NIR irradiation, the nanomotor can still remove the bacteria hidden in the deep biofilm through the targeted action of Ly, ultimately achieving the effect of eradicating MRSA biofilm and promoting DM wound healing.

[0089] (1) Establishment of diabetic mouse model

[0090] The experimental animals used were 5-6 week-old C57 mice, which were fed with standard experimental mouse feed. After one week of adaptive feeding, they were injected with STZ (50 mg kg -1 ), fast for 12 hours before each injection and fast for 2 hours after each injection. Blood sugar was measured 12 hours after the injection, and the fasting blood sugar was greater than 11.1mmol L -1 The DM mouse model was considered successful. All animal operation procedures strictly followed the guidelines and regulations issued by the Experimental Animal Center of Xiangya School of Medicine, Central South University.

[0091] (2) Establishment of diabetic trauma mouse model of MRSA infection

[0092] After fixing the DM mice, shave the back of the mice. Be careful not to scratch the skin during shaving. Then use a depilatory cream to remove the hair on the back of the mice so that the back skin is completely exposed. The next day, use tribromoethanol (240 mg kg- 1 ) were used to anesthetize the mice. After disinfection of the back of the mice, a wound with a diameter of about 8 mm was made on the back of the mice using a sterile biopsy puncher, and 50 μL of MRSA bacterial solution (108 CFU mL-1) was dripped onto the wound surface. 1 ), all surgical procedures were performed under sterile conditions. After 48 hours, a layer of yellow film could be seen on the wound surface, which was the MRSA biofilm, and MRSA-infected diabetic trauma mice were successfully established.

[0093] (3) Animal Experiment Grouping and Treatment

[0094] The mice with successful modeling were divided into the following 6 groups (4 mice in each group): PBS, CS, CSI+NIR, CSIL, CSIL+NIR and vancomycin (Van) groups. The mice in the treatment groups were given injections on their backs for 3 consecutive days (the injection preparations were prepared with normal saline and PBS, CS, CSIL and Van, respectively, and the dosage was 25 mg kg-1). 1 ), CSI+NIR and CSIL+NIR groups were irradiated with NIR for 10 min (1.2 W cm- 2 ), the PBS group and the Van group were treated without treatment after appropriate amounts of PBS and vancomycin were dripped onto the wound. During the NIR treatment group, an infrared thermal imager was used to record temperature changes. During the treatment period, the wounds were photographed and recorded on days 0, 4, 8, 12, and 16. The weight of the mice was recorded every other day, and the mouse bedding was replaced every day. The recorded wound area was measured and analyzed using imaging software. The relative wound area of ​​the mice was calculated according to the following formula:

[0095] Relative wound area (%) = A W / A W0 ×100%

[0096] In the formula, A W A is the wound area of ​​mice on the corresponding days after treatment; W0 is the wound area of ​​mice before treatment.

[0097] The results are as follows Fig.11 As shown, Fig.11(a) shows that before treatment, there was a complete layer of yellow MRSA biofilm on the wound surface of each group of mice, accompanied by exudation, proving that the MRSA infection wound model was successfully established. Treatment was given from 0 to 3 days. On the 4th day, the PBS and CS groups still had complete biofilm and exudation, and the wound surface of the PBS group even had a tendency to expand. The biofilm exudation of the CSI+NIR group was slightly reduced, but the biofilm area of ​​the wound surface did not change significantly. In the CSIL group, both biofilm and exudation were reduced. The obvious change was in the CSIL+NIR treatment group. The yellow biofilm dissolved a lot on the fourth day, but there was still a small amount of exudation, and some exposed red inflammatory tissue could be seen. The biofilm of the Van group still existed stubbornly on the 4th day. The biofilm of the CSI+NIR and Van groups gradually became thinner around the 8th day, but the wound area did not shrink significantly. On the 16th day of treatment, the wounds in the CSIL+NIR group had completely healed, and a small amount of new hair was visible. The biofilms in the PBS and CS groups were thicker and more stubborn than on day 0. There were still some biofilms in the CSI+NIR and Van groups, and the wound healing was poor. A small amount of exudation was still visible on the wound surface of the CSIL group on the 12th day, and it was partially healed on the 16th day.

[0098] In order to more intuitively show the healing situation, the wound surface was drawn and calculated using image software. The relative wound area ratio of the PBS group was 116%, and the area ratios of the CSI+NIR, CSIL, CSIL+NIR and Van groups were 57.8%, 33.2%, 2.8% and 44.3%, respectively, with significant differences (all P < 0.001). This shows that each group has a certain effect on promoting wound healing, but compared with the 2.8% of the CSIL+NIR group, the relative wound area ratios of the other treatment groups were significantly higher than that of the CSIL+NIR group (all P < 0.001) ( Fig.11 b and Fig.11 c), indicating that the wound healing effects of other treatment groups are limited. The above results confirm that the CSIL nanomotor has excellent biofilm removal and wound healing effects in MRSA-infected DM trauma mice when prepared as a drug for promoting diabetic wound healing. It also confirms that the excellent performance of the nanomotor of the present invention is achieved under the synergistic effect of the eccentric structure, ICG, Ly and NIR.

[0099] Example 2

[0100] The difference between this example and Example 1 is that the amount of Ly in step (2) is replaced with 1 mg, and the other steps and conditions are the same. The morphological characteristics of the prepared nanomotor (CSIL) material are consistent with those of Example 1, and it also has an eccentric core-spiny shell core-shell structure, and also has self-thermal drive and MRSA targeting performance, but due to the reduction in the amount of Ly, its antibacterial performance is reduced, and the biofilm is largely dissolved on the 8th day, but the wounds of mice are completely healed after 16 days of treatment.

[0101] Example 3

[0102] The difference between this embodiment and embodiment 1 is that the aminopropylation temperature in step (2) is replaced with 50°C, and the amount of ICG is replaced with 1 mg, and the other steps and conditions are the same. The morphological characteristics of the prepared nanomotor (CSIL) material are consistent with those of embodiment 1, and it also has an eccentric core-spiny shell core-shell structure, and also has self-thermal drive and MRSA targeting performance, but due to the reduction in the amount of ICG, the difference in the intensity of the photothermal effect of each layer of the nanomotor composite material is reduced, and the self-thermal drive rate of the nanomotor is slowed down, but the overall performance is still far better than CS, PBS and Van.

Claims

1. A nanomotor composite material having an eccentric core-spine shell structure, characterized in that: The nanomotor composite material has a core-shell structure, wherein the core is composed of carbon material, the space between the core and the shell is filled with indocyanine green and lysostaphin, the shell is composed of SiO2@carbon material, has a thorny porous structure, and indocyanine green and lysostaphin are loaded on the surface; the sphere centers of the core and the shell do not overlap.

2. The method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 1, characterized in that: The carbon-SiO2@carbon nanoparticles having an eccentric core-spine-shell structure are modified with aminopropyl groups on the surface to obtain aminopropylated carbon-SiO2@carbon nanoparticles; the aminopropylated carbon-SiO2@carbon nanoparticles, indocyanine green and lysostaphin are mixed to obtain a nanomotor composite material having an eccentric core-spine-shell structure; The preparation process of the eccentric core-spiny shell carbon-SiO2@carbon nanoparticles is as follows: aldehyde resin microspheres, resorcinol, formaldehyde and tetraethyl orthosilicate are reacted A to obtain nanospheres with a core-shell structure, phenolic resin-SiO2@phenolic resin; an etchant is added to the phenolic resin-SiO2@phenolic resin for hydrothermal reaction to obtain partially etched phenolic resin-SiO2@phenolic resin nanospheres; the partially etched phenolic resin-SiO2@phenolic resin nanospheres are obtained after carbonization.

3. The method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 2, characterized in that: The phenolic resin microspheres are obtained by polycondensation reaction of resorcinol, formaldehyde and water under the action of an alkaline catalyst.

4. A method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 2 or 3, characterized in that: The process of surface grafting modification with aminopropyl groups is as follows: after dispersing carbon-SiO2@carbon nanoparticles, (3-aminopropyl)triethoxysilane is added to carry out grafting reaction; The solid-liquid ratio of carbon-SiO2@carbon nanoparticles and (3-aminopropyl)triethoxysilane is 15 mg: (0.15-0.3) mL.

5. The method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 4, characterized in that: The conditions for the surface grafting modification of aminopropyl groups are: temperature of 50-60° C. and time of 10-12 hours.

6. The method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 2, characterized in that: The mass ratio of the aminopropylated carbon-SiO2@carbon nanoparticles, indocyanine green and lysostaphin is 2:(0.125-2):(0.125-2); The mixing conditions are: stirring at room temperature for 24 to 48 hours.

7. The method for preparing a nanomotor composite material having an eccentric core-spine shell structure according to claim 2, characterized in that: The conditions of reaction A are: room temperature, reaction time 5-6 hours; the conditions of the hydrothermal reaction are: temperature 70-80°C, time 0.5-2 hours, and the etchant includes Al(NO3)3 solution; The carbonization conditions are: temperature of 500-550° C. and time of 2-3 hours.

8. The use of a nanomotor composite material having an eccentric core-spine shell structure as claimed in claim 1, characterized in that: The invention is used for preparing medicines for promoting diabetic wound healing.

9. The use of a nanomotor composite material having an eccentric core-spine shell structure according to claim 8, characterized in that: The medicine comprises a nano motor composite material with an eccentric core-spiny shell structure, physiological saline and auxiliary materials.

10. Use of a nanomotor composite material having an eccentric core-spine shell structure according to claim 8 or 9, characterized in that: The drug has a photothermal effect, and infrared light irradiation is used in the early stage of the drug action process, and no infrared light irradiation is used in the later stage.

Citation Information

Patent Citations

  • Enzyme-driven bottle-shaped nano-motor and preparation method thereof

    CN108524941A

  • Janus nanoparticle and preparation method and application thereof

    CN108822302A

  • Photodynamic combined lysozyme antibacterial method

    CN112618716A

  • Nanometer motor composite material and preparation method and application thereof

    CN117653747A